(untitled) (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted to collect the information on array of existing breeding and health care practices followed by dairy animal owners of coastal area of South Gujarat. Perusal of data revealed that the majority of respondents (98.7%) relied on behavioral signs of heat as a method of heat detection. They preferred artificial insemination process (86%) for breeding their animals. For majority of indigenous cattle & buffalo calving interval was more than 15 months (86.7%) and 16-18 months (56.7%), respectively. Majority of respondents (88.7%) were following the vaccination programme against F.M.D. & H.S. for their animals. About 71% of the respondent followed the practices (dusting, spraying, injectable drugs) to control ecto-parasites. The animal shed was clean and dry for about 85.3 % of the respondents. Except few overall dairy animal owners were following more scientific and organized herd management practices in the coastal area of South Gujarat.